The Significance of Duration Weighted Neighborhood Effects for Violent Behavior and Explanation of Ethnoracial Differences - Bellair, Paul E. (Journal of quantitative criminology, 2025)
PurposeTwo important issues constrain the neighborhood effects literature. First, most prior research examining neighborhood effects on aggression and self-reported violence uses a point in time (i.e., cross-sectional) estimate of neighborhood disadvantage even though the duration of exposure to neighborhood disadvantage varies between families. Second, neighborhood effects may be understated due to over-controlling for family socioeconomic conditions. Both limitations suggest that prior research may be underestimating neighborhood effects, which impacts research on the invariance thesis and explanation of ethnoracial differences.MethodsThe sample is drawn from the restricted use Future of Families and Child Well-being study. Data to measure youth’s exposure to neighborhood disadvantage is drawn from birth through age 9, with dependent variables measured at age 15. We estimate marginal structural models (MSM) with inverse probability of treatment weights (IPTW.ResultsThe results support hypotheses, indicating that the duration weighted measure of neighborhood disadvantage is more strongly associated with aggression and self-reported violence than the point in time, and that it accounts for a larger share of the ethnoracial differences.ConclusionsThe findings provide a clear image of the consequences of long-term exposure to neighborhood disadvantage for aggression and violence. They suggest that criminologists addressing neighborhood effects should attempt, when feasible, to document and model the duration of exposure to neighborhood disadvantage. They are also consistent with and add to a growing literature addressing MSM modeling with IPTW weights.